TISUS texts - Sundberg Gunlög; Lundkvist Peter (University of Gothenburg, 2024)
For access please contact Elena Volodina.

För åtkomst kontakta Elena Volodina.
TISUS-texter
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik